Integrate target cost techniques and value chain analysis to achieve competitive advantage - Abdulmahdi Abdulhusein Idan, Abdulrasool Abaulabbas Sahib, Azdehar J. Mohammed AL-kuwair, (Opción, 2019)
This paper aims to check the philosophy of target cost accounting and continuous improvement techniques with a sign of the aspects of integration between them and its importance in achieving prices reduction and competitive advantage for the organization via the descriptive analytical approach. As a result, the techniques of target cost accounting and continuous improvement area unit among the foremost vital techniques of strategic price management moving the company's success to the implementation of it competitive methods. In conclusion, by the adoption of target cost accounting technique, the market was the most determinant of value instead of price.